Chronic Kidney Disease from Pathophysiology to Clinical Improvements - Rath, Thomas (IntechOpen, 2018)
Known worldwide, chronic kidney disease (CKD) is a disease that affects up to 4% of the population with increasing figures also in the developing countries. Life expectancy of patients affected by CKD is shortened compared to the overall population, and only a minority of patients reach end-stage renal disease (ESRD) with the need for dialysis or renal transplantation; death overtakes dialysis. In the 13 chapters, this book sheds light on the different aspects related to pathophysiology and clinical aspects of CKD, providing interesting insights into not only inflammation and cardiovascular risk but also the interplay of hormones and the functional aspects of endothelial function. In addition, chapters dealing with genetic aspects of polycystic kidney disease and also the clinical handling of patients with CKD and peritoneal dialysis will be beneficial for the open-minded reader.